THE PREPARATION OF TWO AROMATIC ANALOGS OF DESOXYCORTICOSTERONEACETATE - SCHOLZC, R; DJERASSI, CARL (CIBA PHARMACEUTICAL PRODUCTS, RESEARCH DEPARTMENT DIVISION OF CHEMISTRY, SUMMIT, NJ, EUA, 1949)
Two syntheses of 3-methoxy-17-(Î²-acetoxyacetyl)-1,3,5-estratriene (III), an aromatic analog of desoxycorticosterone acetate, are described. The first procedure involved hydroxylation of 17-vinylestradiol methyl ether (Vb) with osmium tetroxide followed b
JOURNAL ROYAL HORTICULTURAL SOCIETY LONDON
Keywords: PREPARATION, TWO AROMATIC ANALOGS, DESOXYCORTICOSTERONEACETATE; QUIMICA; QUIMICA ORGANICA; HIDROCARBUROS AROMATICOS